A Study on Prescription Pattern and Assessment of Smoking as a Risk Factor among COPD Patients in a Tertiary Care Hospital - Sharma, Monika; Singh, Rajesh Kumar (Journal of Pharmacy Practice and Community Medicine)
The present study highlights the impact of Mobile-learning (M-learning) on a global scale during the COVID-19 pandemic. The government has executed lockdown to meet the guidelines of social distancing and to prevent its further wide spreadability. It resulted in the suspension of all activities globally. Significantly, the education system has been affected to a large extent. Amid this epidemic, M-learning has played an imperative role in the education system, especially in the pharmacy sector. Technological integration in learning and education is an integral part of the ever-changing technological world. In this article, we discussed the role of mobile technology in higher education, especially in the research areas. The study aims to explore and emphasize different strategies of mobile learning used to promote student education. It mainly acts by integrating various M-learning tools (Knowledge software, mobile applications) with the future view on education using informatics. This study analyzes the existing literature based on M-learning perspectives, benefits, limitations and challenges.
Keywords: Mobile learning (M-learning); E-learning (Electronic learning); D-learning (Digital or distance learning); Smartphones; Mobile technology; Pharmacy education; COVID-19; mHealth; Telehealth; Gamification